2018
DOI: 10.1002/ejsp.2550
|View full text |Cite
|
Sign up to set email alerts
|

A model for predicting prejudice and stigma expression by understanding target perceptions: The effects of visibility, politicization, responsibility, and entitativity

Abstract: The study of hostile orientations toward outgroups is divided into three main domains: (i) overt (explicit, old‐fashioned, or hostile) prejudice; (ii) veiled (implicit, modern, aversive, or subtle) prejudice, and (iii) stigma. To date, there is no systematic account of which form of hostility is likely to be expressed toward members of particular target groups. We propose a model that integrates the two forms of prejudice and the concept of stigma into a single framework. The contingency model of stigma and pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 107 publications
1
14
0
2
Order By: Relevance
“…On the other hand, when seeking to measure individuals’ stereotypical beliefs about target groups (e.g., when testing the effectiveness of prejudice reduction interventions), instruction from a personal perspective seems to be an adequate choice. In fact, a comparison between individual stereotypical beliefs and perceptions of shared cultural stereotypes could become a useful operationalization for assessing the “normative climate” ( Váradi, 2014 ; Forscher et al, 2015 ) or “normative context” ( Kende et al, 2017 ; Kende and McGarty, 2019 ). The concept of “normative climate” would allow for studying the attitude-social norm context in which stereotypes and prejudice toward different target groups are expressed or withheld.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when seeking to measure individuals’ stereotypical beliefs about target groups (e.g., when testing the effectiveness of prejudice reduction interventions), instruction from a personal perspective seems to be an adequate choice. In fact, a comparison between individual stereotypical beliefs and perceptions of shared cultural stereotypes could become a useful operationalization for assessing the “normative climate” ( Váradi, 2014 ; Forscher et al, 2015 ) or “normative context” ( Kende et al, 2017 ; Kende and McGarty, 2019 ). The concept of “normative climate” would allow for studying the attitude-social norm context in which stereotypes and prejudice toward different target groups are expressed or withheld.…”
Section: Discussionmentioning
confidence: 99%
“…These beliefs resemble old-fashioned prejudice, which research on racism suggested was declining since the 1980s (see McConahay, 1983). The fact that Roma people are still seen through traditionally negative stereotypes may be explained by the specific target perceptions (i.e., prejudice content) that the majority population have about the Roma, which can justify the overt expression of prejudice (for a review on target perceptions and prejudice expression, see Kende & McGarty, 2019). The perceived Undeserved Benefits subscale of the ATRS, which contains items mostly adopted from scales of modern racism, reveals that Roma people are also considered competitors for limited resources, and therefore represent a tangible threat (see Stephan & Stephan, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Decades of research suggest the prevalence of modern (McConahay, 1983), subtle (Pettigrew & Meertens, 1995), implicit (Banaji & Greenwald, 1994), and aversive (Dovidio & Gaertner, 1986) expressions of ethnic and racial prejudice over old-fashioned, blatant, explicit, and hostile forms in contemporary democratic societies. However, evidence of prejudice and hate crimes against the Roma suggests otherwise: anti-Gypsyism remains hostile and openly negative (for a critique of interpreting overt forms of prejudice as a phenomenon of the past, see Kende & McGarty, 2019; Leach, Peng, & Volckens, 2000). For instance, Kende et al (2017) showed that prejudice against the Roma is expressed overtly in East-Central Europe because societal norms approve of it.…”
Section: Anti-gypsyism Across Europementioning
confidence: 99%
“…Because intergroup bias and stereotypes are integral parts of stigma, a higher perceived entitativity of a group may precondition the formation of stigmatized attitudes towards the group. Kende and McGarty [ 55 ] recently formulated a contingency model about stigma and prejudice expression, in which entitativity featured prominently as a key node in determining the stigma expression. There is also evidence showing that perceived entitativity could affect the responses to stigma among persons with mental illness [ 47 , 56 ].…”
Section: Introductionmentioning
confidence: 99%